Electrode Consumption Simulation for Shielded Metal Arc Welding in Virtual Welding Training System - Al-Sabur, Raheem Kh.; Machine, The construction Virtual Welding Training; Rishack, Qais A. (Basrah Journal for Engineering Sciences, 2014)
One of the major problems in industry are new welding trainees cost, it drains the budget of many companies, particularly in industrialized countries, through raw material costs for preparation, welding wires, electric and fumes in addition to time spent. Recently a new technique was appeared; it is called virtual welding training system (VWTS) to reduce the training cost. In the present work a VWTS technique was built, a simulation of electrode motion is upgraded by using LVDT to represent the welding arc length while a DC motor with gearbox connect to the steel rode is used to represent welding electrode consumption. A 2D graphs with touch screen monitor are used to represent welding process. All sensors were calibrated to generate a VWTS. Accepted results obtained in training new welding trainees in the shielded metal arc welding (SMAW) training.